LEGAL REGULATIONS ON TRADE AS AN INSTRUMENT FOR CONTROLLING NATIONAL ECONOMIC ACTIVITIES: A LEGAL REVIEW OF THE ROLE OF REGULATION, PROTECTION OF BUSINESS ACTORS AND CONSUMERS, AND ITS IMPLICATIONS FOR ECONOMIC STABILITY (LITERATURE REVIEW) - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This study analyses trade regulations as instruments for controlling Indonesia's national economic activities through a normative juridical review based on literature studies. Using a legislative approach to Law No. 7 of 2014 on Trade, Law No. 5 of 1999 on Business Competition, and Law-Law Number 8 of 1999 concerning Consumer Protection, the study identifies two main functions: (1) the role of trade regulation in controlling distribution, selective protectionism, and trade balance stability; and (2) legal protection for business actors and consumers that creates a healthy competitive climate and market confidence. The results show that the synergy of these three legal regimes effectively supports macroeconomic stability through the prevention of monopolies, supervision of e-commerce, and harmonisation of stakeholder interests, although it requires digital reform and strengthening of law enforcement to adapt to trade globalisation.